The great war for civilisation the conquest of the Middle East - Fisk, Robert (Vintage Books, 2007)
"Reaching back into the long history of invasion, occupation and colonization in the region, Robert Fisk sets forth information in a way that makes clear how a history of injustice "has condemned the Middle East to war." He lays open the role of the West in the seemingly endless strife and warfare in the region, traces the growth of the West's involvement and influence there over the past one hundred years, and outlines the West's record of support for some of the most ruthless leaders in the Middle East. He chronicles the ever-more-powerful military presence of the United States and tracks the consequent, increasingly virulent anti-Western - and particularly anti-American - sentiment among the region's Muslim populations.